Interactions of vanadium(V)–citrate complexes with the sarcoplasmic reticulum calcium pump - Aureliano, M. (2012)
Among the biotargets interacting with vanadium is the calcium pump from the sarcoplasmic reticulum (SR). To this end, initial research efforts were launched with two vanadium(V)–citrate complexes, namely (NH4)6[V2O4(C6H4O7)2] Æ 6H2O and (NH4)6[V2O2(O2)2(C6H4O7)2] Æ 4H2O, potentially capable of interacting with the SR calcium pump by combining kinetic studies with 51V NMR spectroscopy. Upon dissolution in the reaction medium (concentration range: 4–0.5 mM), both vanadium(V):citrate (VC) and peroxovanadium(V):citrate (PVC) complexes are partially converted into vanadate oligomers. A 1 mM solution of the PVC complex, containing 184 lM of the PVC complex, 94 lM oxoperoxovanadium(V) (PV) species, 222 lM monomeric (V1), 43 lM dimeric (V2) and 53 lM tetrameric (V4) species, inhibits Ca2+ accumulation by 75 %, whereas a solution of the VC complex of the same vanadium concentration, containing 98 lM of the VC complex, 263 lM monomeric (V1), 64 lM dimeric (V2) and 92 lM tetrameric (V4) species inhibits the calcium pump activity by 33 %. In contrast, a 1 mM metavanadate solution, containing 460 lM monomeric (V1), 90.2 lM dimeric (V2) and 80 lM tetrameric (V4) species, has no effect on Ca2+ accumulation. The NMR signals from the VC complex ( 548.0 ppm), PVC complex ( 551.5 ppm) and PV ( 611.1 ppm) are broadened upon SR vesicle addition (2.5 mg/ml total protein). The relative order for the half width line broadening of the NMR signals, which reflect the interaction with the protein, was found to be V4 > PVC > VC > PV > V2 = V1 = 1, with no effect observed for the V1 and V2 signals. Putting it all together the effects of two vanadium( V)–citrate complexes on the modulation of calcium accumulation and ATP hydrolysis by the SR calcium pump reflected the observed variable reactivity into the nature of key species forming upon dissolution of the title complexes in the reaction media.